2021
DOI: 10.1007/s00216-021-03500-7
|View full text |Cite
|
Sign up to set email alerts
|

Feature-based molecular networking for identification of organic micropollutants including metabolites by non-target analysis applied to riverbank filtration

Abstract: Due to growing concern about organic micropollutants and their transformation products (TP) in surface and drinking water, reliable identification of unknowns is required. Here, we demonstrate how non-target liquid chromatography (LC)-high-resolution tandem mass spectrometry (MS/MS) and the feature-based molecular networking (FBMN) workflow provide insight into water samples from four riverbank filtration sites with different redox conditions. First, FBMN prioritized and connected drinking water relevant and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 59 publications
(92 reference statements)
0
13
0
Order By: Relevance
“…Unexpectedly, more features were prioritized for data in negative ionization mode compared to that in positive mode, which is surprising as many NTS monitoring studies include only measurements in a positive mode. 5,7,9,28 This emphasizes that measurements in a negative ionization mode should not be neglected in NTS studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unexpectedly, more features were prioritized for data in negative ionization mode compared to that in positive mode, which is surprising as many NTS monitoring studies include only measurements in a positive mode. 5,7,9,28 This emphasizes that measurements in a negative ionization mode should not be neglected in NTS studies.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Spring samples showed a higher number of prioritized features compared to Summer , which might be explained by higher pesticide applications in this period. Unexpectedly, more features were prioritized for data in negative ionization mode compared to that in positive mode, which is surprising as many NTS monitoring studies include only measurements in a positive mode. ,,, This emphasizes that measurements in a negative ionization mode should not be neglected in NTS studies.…”
Section: Results and Discussionmentioning
confidence: 99%
“…), increasing the link between peak picking algorithms and in silico annotation tools [ 12 ]. Until now, FBMN has been successfully applied in various fields of metabolomics, allowing level II/level III identification of transformation products of organic micropollutants in water samples [ 13 ], native plant constituents [ 14 , 15 , 16 ], and endogenous urinary metabolites [ 17 ]. However, mass spectral library matching is generally performed by the comparison with mass spectral libraries containing MS/MS spectra acquired under a wide range of instrumental conditions (e.g., time-of-flight, orbitrap, hybrid ion traps, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…However, mass spectral library matching is generally performed by the comparison with mass spectral libraries containing MS/MS spectra acquired under a wide range of instrumental conditions (e.g., time-of-flight, orbitrap, hybrid ion traps, etc.) and collision energies used, with different curation protocols providing different mass accuracy levels [ 13 , 16 ], thus suffering from limited reliability of the annotation due to differences in observed mass fragments and their intensity ratios. This issue can be managed by implementing better contextualized libraries containing reference spectra of study-related compounds and acquired under experimental conditions equal to or comparable to the experimental data being analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…), increasing the link between peak picking algorithms and in silico annotation tools (Nothias, Petras, Schmid, Dührkop, Rainer, Sarvepalli, et al, 2020). Until now, FBMN has been successfully applied in various fields of metabolomics, such as the identification of transformation products of organic micropollutants in water samples (Oberleitner, Schmid, Schulz, Bergmann, & Achten, 2021), native plant constituents (Padilla-González, Sadgrove, Ccana-Ccapatinta, Leuner, & Fernandez-Cusimamani, 2020;Rivera-Mondragón, Tuenter, Ortiz, Sakavitsi, Nikou, Halabalaki, et al, 2020;Xie, Kong, Li, Nothias, Melnik, Zhang, et al, 2020) and endogenous urinary metabolites (Neto & Raftery, 2021;Quinn, Melnik, Vrbanac, Fu, Patras, Christy, et al, 2020), while no applications have been reported till now in nutrimetabolomics.…”
Section: Introductionmentioning
confidence: 99%